Dampak Penggunaan E-learning Selama Pandemi Covid-19 Terhadap Tingginya Angka Penderita Miopi - Muhammad Hazel Bayu Perkasa; Novian Arif Ramadhan; Naudiana Wihadini; Iqlima Pratiwi (Flourishing Journal, 2022)
Learning using e-learning during the Covid-19 pandemic has made the learning system in schools online. The learning system causes the intensity of our eyes to see the screen to increase which causes an increase in the number of myopia sufferers. Myopia is one of the health problems that can cause blindness. Therefore, we wrote this article to examine the impact of using e-learning during the Covid-19 pandemic on the high number of people with myopia. This article uses the literature review method through journals that are relevant to the topic discussed. The results of this study prove that the number of myopia sufferers increased by 59.35% during the Covid-19 pandemic. The implementation of lockdown makes the learning system carried out using online e-learning methods make us stare at gadget screens beyond the capacity of our eyes which causes a reduction in the sharpness of our eyes. In addition, reduced activity outside the home leads to an increase in the number of diopters associated with the development of myopia symptoms. In patients with myopia, there is a longer axial length that adds to the effect of secondary ocular sequelae, making a person experience eye disorders that are difficult to cure. Abstrak Pembelajaran menggunakan e-learning selama pandemi Covid-19 membuat sistem belajar di sekolah menjadi online. Sistem pembelajaran tersebut menyebabkan intensitas mata kita melihat layar meningkat yang menyebabkan bertambahnya angka penderita miopi. Miopi merupakan salah satu gangguan kesehatan yang dapat menyebabkan kebutaan. Maka dari itu, artikel ini kami tulis untuk mengkaji dampak penggunaan e-learning selama pandemi Covid-19 terhadap tingginya angka penderita miopi. Artikel ini menggunakan metode literature review melalui jurnal-jurnal yang relevan dengan topik yang dibahas. Hasil dari penelitian ini membuktikkan bahwa angka penderita miopi bertambah sebesar 59,35% selama pandemi Covid-19. Penerapan lockdown membuat sistem pembelajaran dilakukan menggunakan metode e-learning secara online membuat kita menatap layar gadget melebihi kapasitas mata kita yang menyebabkan berkurangnya ketajaman mata kita. Selain itu, berkurangnya aktivitas di luar rumah menyebabkan peningkatan pada jumlah dioptri yang berhubungan dengan perkembangan gejala miopia. Pada pasien dengan miopi terdapat panjang aksial yang lebih panjang sehingga menambah efek gejala sisa okuler sekunder sehingga membuat seseorang mengalami gangguan mata yang susah disembuhkan.